Electrospun nanofibrous interleaves for improved low velocity impact resistance of glass fibre reinforced composite laminates. (5th March 2018) - Daelemans, Lode; Cohades, Amaël; Meireman, Timo; Beckx, Jasper; Spronk, Siebe; Kersemans, Mathias; De Baere, Ives; Rahier, Hubert; Michaud, Véronique; Van Paepegem, Wim; De Clerck, Karen
Abstract: This study analyses the damage tolerance of nanofibre interleaved composites when subjected to low velocity impact. Cross-ply glass/epoxy composite laminates are produced. Drop-weight impact and residual compressive strength measurements are performed on these laminates according to the ASTM D7136 and ASTM D7137 standards for a range of impact energies around the Barely Visible Impact Damage energy limit. Polyamide 6, polyamide 6.9 and polycaprolactone nanofibrous veils with two different veil densities are selected to assess their effect on the damage tolerance. The low velocity impact resistance of nanofibre interleaved laminates increases considerably compared to the virgin material. The (projected) damage area decreases up to 50–60%, especially at higher impact energies where the virgin material shows widespread delamination. As more energy is absorbed in the interleaved laminates by the nanofibres, less damage to reinforcing fibres and matrix resin is produced. Analysis of fracture surfaces shows that the development of nanofibre bridging zones is the main reason for the improved impact damage tolerance. Graphical abstract: Image 1 Highlights: Electrospun nanofibrous veils are effective at increasing the impact tolerance. Polycaprolactone nanofibres result in better impact resistance than polyamide nanofibres. Nanofibre toughened interlayers result in reduced damage area and an increased Barely Visible Impact Damage region. Nanofibre bridging zones are the main toughening mechanism during impact failure. Compression after impact strength not negatively affected.